Dampak Penggunaan Gadget Pada Perkembangan Sosial Anak Usia Dini - Siti Aminah (JCE (Journal of Childhood Education), 2025)
Age 3-6 years is an important period in early childhood development. Various stimulations received by early childhood, including the use of gadgets, can influence various dimensions of their development, one of which is social emotional development. This qualitative field research aims to identify the influence of gadget use on the social development of early childhood in Sidotopo Village, Surabaya. The subjects involved in this study were 10 parents who have children or close relatives of an early age who interact with gadgets on a daily basis. Data collection was conducted through participatory observation and in-depth interviews. The results of the study showed: 1) the forms of gadget use by early childhood in Sidotopo Village, Surabaya are mostly for watching videos via the Youtube application and for accessing games. The videos and games can be for entertainment or related to children's learning activities. 2) the impact of gadget use on the social emotional development of early childhood can be positive or negative. This depends on the type of video or game accessed by the child, the intensity and duration of use, and the involvement or supervision of parents in the use of the gadget. The use of gadgets has a positive impact if the application or video accessed can help the learning process or stimulate the child's development, with limited intensity and duration of use accompanied by parental supervision. The negative impact of gadget use appears especially when there is no parental control or supervision in selecting video or game content, as well as no control over the duration or intensity of use. The forms of negative impacts of gadget use on the social emotional development of early childhood in Sidotopo Village, Surabaya, one of which is the tendency to imitate aggressive behavior from the videos/games accessed.